Information Communication Technology (ICT) Policy of Sri Lanka and its Impacts to Socioeconomic Development: A Review of Sri Lankan Experience - Ravindra, D. M. (Journal of Education and Vocational Research, 2011)
The ICT policy of Sri Lanka has been largely contributed by both local and international institutions with the holistic purpose of enhancing quality of mass and providing sustainable outset for a knowledge society. The methodology followed by the author was secondary data review and the review report discusses the origin of ICT policy and how it integrates with broad set of stakeholders especially with education, government, industry and masses of Sri Lanka. This article provides a review of how successfully Sri Lanka initiates working programmes by the support of institutions accompanied with new policy frameworks. The key insight of this review article educates the importance of strategic implementation of ICT to strengthening country development plans operating as a value adding hub to industries and communities. The contribution of ICT as an enabler to succeed different sectors has been discussed under different segments. Finally, it concludes the way and progress what ICT should have in future to broadening opportunities for third world countries.